Advance Directives: Patient Preferences in Family Practice - Sloan, John P. (1990)
The author reports on six months' experience of obtaining advance directives from patients for care in a family practice. Patients were questioned about their preferences for comfort or prolonging life and then were asked to delegate a substitute decision maker. Of 20 patients, all who responded chose comfort over prolonging life. Delegated substitute decision makers included spouses, children, and professionals or friends. In this population, patients overwhelmingly favoured comfort over prolonging life in the event that they might be irreversibly disabled, and they tended to choose spouses or other first-degree relatives as substitute decision makers.